The association between serum vitamin D and body composition in South African HIV-infected women - Samuel Mwango; Janet Carboo; Christa Ellis; Marike Cockeran; Carina M.C. Mels; Herculina S. Kruger (AOSIS, 2021)
Background: HIV and antiretroviral therapy (ART) alter vitamin D metabolism, and may be associated with bone loss. Objectives: The aim of this study was to determine the association between serum 25-hydroxyvitamin D (25(OH)D) and body composition in postmenopausal South African women living with HIV and on ART. Method: In this 2-year longitudinal study on 120 women conducted in the North West province of South Africa, serum 25(OH)D concentration, bone mineral density (BMD) at three sites, lean mass and percentage of body fat (%BF) were measured by dual-energy X-ray absorptiometry (DXA). Multivariable linear mixed models were used to assess the association between serum 25(OH)D and body composition over 2 years. Linear mixed models were also used to determine the longitudinal association between lean mass, %BF and BMD. Results: Vitamin D deficiency and insufficiency increased from baseline (10.2% and 19.5%) to 11.5% and 37.5%, respectively, after 2 years. Serum 25(OH)D decreased significantly, however, with a small effect size of 0.39 (P = 0.001), whilst total BMD (effect size 0.03, P = 0.02) and left hip femoral neck (FN) BMD (effect size 0.06, P = 0.0001) had significant small increases, whereas total spine BMD did not change over the 2 years. Serum 25(OH)D had no association with any BMD outcomes. Lean mass had a stronger positive association with total spine and left FN BMD than %BF. Conclusion: Serum 25(OH)D was not associated with any BMD outcomes. Maintenance of lean mass could be important in preventing bone loss in this vulnerable group; however, longer follow-up may be necessary to confirm the association.